2016
DOI: 10.1021/acs.jpcc.6b07734
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Dependent Morphology and Optical Properties of Lead Sulfide Quantum Dot Superlattices

Abstract: Small angle X-ray scattering, atomic force microscopy, optical microscopy, and absorption and luminescence spectroscopy have shown that the type and amount of surface organic ligands have a strong impact on the morphology and optical properties of 2D superlattices formed by lead sulfide quantum dots (QDs) of different sizes deposited on a glass substrate. This allows control of the process of QD self-assembly, the homogeneity of the superlattices, and the interparticle distance by optimization of the amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…After ten days, the steady-state parameters of the PL remained unchanged. We assume that there is a slight decrease in the size of QD core, similar to observed for the PbS QD superlattices, 39 accompanied with a change in the dielectric permittivity of the surrounding media compared to the QD solution, which may result in the blue shift of the QD PL band. The observed trend in the PL agrees with the results of morphological studies of the SCs.…”
Section: Optical Properties Of Superstructuresmentioning
confidence: 63%
“…After ten days, the steady-state parameters of the PL remained unchanged. We assume that there is a slight decrease in the size of QD core, similar to observed for the PbS QD superlattices, 39 accompanied with a change in the dielectric permittivity of the surrounding media compared to the QD solution, which may result in the blue shift of the QD PL band. The observed trend in the PL agrees with the results of morphological studies of the SCs.…”
Section: Optical Properties Of Superstructuresmentioning
confidence: 63%
“…We can speculate that the removal of oleic acid during the ligand exchange plays a crucial role for the film formation. It has been recently shown that the amount of oleic acid can influence the self-organization of QD superstructures [37][38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 99%
“…29,30 Optical, electrical, thermal and mechanical properties of such QDSLs are thus determined not only by individual QDs, but also by the dimensionality dependent resonant couplings through the interior nano space among adjacent QDs tuned by ligand engineering down to subnanometer regime. 3,14,19,[31][32][33][34][35][36][37][38] Thus, the dimensionality in the QDSLs should be a crucial parameter for independent tailoring of the electronic and photoexcited properties including the multiple exciton generation (MEG) through which multiple electron-hole pairs can be produced; [39][40][41] the MEG is expected to increase solar cell efficiency by creating multiple carriers from a single photon absorption. 42 Meanwhile, temperature can be another important parameter to control the physical properties of the QDSLs.…”
Section: Introductionmentioning
confidence: 99%